High‐frequency vibration characteristic of Pb0.97La0.02(Zr0.95Ti0.05)O3 anti‐ferroelectric thick films cantilever. (1st December 2016) - An, Kun; Zhang, Hui; Chou, Xiujian; Xue, Chenyang; Zhang, Wendong
Abstract : A Pb0.97 La0.02 (Zr0.95 Ti0.05 )O3 anti‐ferroelectric thick‐film micro‐cantilever applying micro‐machining technology based silicon was designed and fabricated to meet the requirements of high‐frequency vibration energy application. The anti‐ferroelectric cantilevers showed the high‐frequency vibration characteristics with the strain generated due to the anti‐ferroelectric–ferroelectric transformation. The maximum vibration velocity and displacement of the cantilever tip of 600 μm (L) × 60 μm (W) × 10 μm (H) were 4.22 m/s and 23.5 μm. The first response frequency was up to 28.6 kHz at 42 V transitions voltage induced when the anti‐ferroelectric material layer was strained, significantly larger than the typical piezoelectric cantilevers. The five‐size different cantilevers fabricated in one chip had mostly the same sharp voltage, owing to the same thickness of anti‐ferroelectric material layer. The vibration frequency increased with the decrease of the cantilever length, while the vibration velocity and displacement had the opposite trends. It can be seen that the silicon‐based anti‐ferroelectric cantilever with a high vibration frequency shows a more incomparable vibration than other cantilevers of other materials, which can be regarded as a new direction for micro‐electro‐mechanical system vibration devices.